Toughening of Carbon Fiber Based Composites With Electrospun Fabric Layers - Beylergil, Bertan; Beylergil, Bertan; Aktaş, Engin; Tanoğlu, Metin (Izmir Institute of Technology, 2017)
The objective of this PhD thesis is to investigate interlaminar Mode-I fracture toughness of carbon fiber/epoxy composites interleaved by micro and/or nano scaled PA66 nonwoven veils. Also, the effects of electrospun PVA nanofibers on the mechanical performance of these composites were investigated. Additionally, this thesis also deals with the effects of aramid nonwoven veils on the mechanical properties of CF/EP composites. The produced nanofibers produced by electrospinning were directly deposited on carbon fiber fabrics. Then, reference and nano-modified laminates were manufactured by vacuum infusion method. A series of mechanical tests such as tensile, compression, three point bending, Charpy-impact, interlaminar shear strength and open hole tensile tests (OHT) were carried out on the prepared specimens. Double cantilever beam (DCB) tests were conducted on reference and interleaf-modified laminates. The effect of PA 66 nanofiber areal weight density was also evaluated with varying electrospinning time. Scanning electron microscopy (SEM) was used to investigate the fiber morphology and to understand the toughening mechanisms. Dynamic mechanic analysis (DMA) was used to investigate the thermo-mechanical behavior of reference and interleaf-modified composite specimens. Differential scanning calorimetry (DSC) was used to determine the thermal properties of micro and electrospun PA66 nonwoven veils. Comparing the mechanical test results, the most effective nonwoven interleaving system was determined in terms of higher delamination resistance and in-plane mechanical properties. Finite element method (FEM) was used to evaluate the effects of electrospun PA66 nonwoven veils on the CF/EP composites. Numerical simulations of Mode-I fracture toughness tests were carried out using ANSYS Workbench. The results showed that the most effective material was electrospun PA66 nonwovens considering the higher delamination resistance. Additionally, the electrospun PA 66 nonwovens also improved Charpy-impact and interlaminar shear strength of the reference CF/EP composites. Numerical results showed good agreement with the experimental ones.

Bu doktora tezinin amacı, arayüzeyde mikro ve/veya nano boyutta poliamid 66 (PA 66) dokusuz kumaş tabakaları kullanılarak üretilmiş karbon fiber/epoksi (KF/EP) kompozitlerin Mod-I kırılma tokluğunun incelenmesidir. Ayrıca, elektroeğrilmiş polivinil alkol (PVA) nanofiberlerin bu kompozitlerin mekanik performansı üzerine etkileri incelenmiştir. Buna ek olarak, bu tezde aramid dokusuz kumaşlar kullanılarak üretilmiş KF/EP kompozitlerin mekanik özellikleri incelenmiştir.Üretilen nanofiberler direkt olarak karbon kumaş üzerine kaplanmıştır. Daha sonra referans ve nanofiber takviyeli kompozitler vakum infüzyon yöntemiyle üretilmiştir. Üretilen numunelere çekme, basma, üç-nokta eğme, Charpy-darbe, arayüzey kayma mukavemeti ve delikli çekme testleri yapılmıştır. Referans ve arayüzeyi modifiye edilmiş numunelere Çift Ankastre Kiriş Testleri (DCB) yapılmıştır. PA 66 nanofiber alansal yoğunluğunun etkisi elektroeğirme süresi değiştirilerek ortaya konmuştur. Taramalı elektron mikroskobu kullanılarak fiber morfolojisi ve arayüzey kırılma mekanizmaları incelenmiştir. Dinamik mekaniz analiz (DMA) ile referans ve arayüzeyi modifiye edilmiş kompozit numunelerin termomekanik özellikleri incelenmiştir. Diferansiyel taramalı kalorimetre (DSC) yöntemiyle mikro ve elektroeğrilmiş PA66 dokusuz kumaşların termal özellikleri belirlenmiştir. Mekanik test sonuçları karşılaştırılarak, delaminasyon direnci ve düzlem-içi mukavemet açısından en verimli dokusuz kumaş sistemi belirlenmiştir. Buna ek olarak sonlu elemanlar yöntemi ile elektroeğrilmiş PA 66 nanokumaş tabakaların KF/EP kompozitler üzerine etkisi incelenmiştir. Mod- I kırılma tokluğu testlerinin nümerik simülasyonları ANSYS Workbench kullanılanılarak gerçekleştirilmiştir. Sonuçlar en verimli sistemin elektroeğrilmiş PA66 dokusuz kumaşlar olduğunu göstermiştir. Buna ek olarak, bu kumaşların referans KF/EP kompozitlerin darbe direncini ve arayüzey mukavemetini iyileştirdiği gözlemlenmiştir. Nümerik sonuçların deneysel sonuçlarla uyum gösterdiği belirlenmiştir.
Elektroeğrilmiş Kumaş Tabakaları ile Karbon Elyaf Esaslı Kompozitlerin Toklaştırılması
Thesis (Doctoral)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2017
Full text release delayed at author's request until 2020.11.21
Includes bibliographical references (leaves: 148-158)
Text in English; Abstract: Turkish and English
Keywords: Nanofibers; Carbon fibers; Polymer composite; Electrospinning; Polyvinyl alcohols